A Gelatin-sulfonated Silk Composite Scaffold based on 3D Printing Technology Enhances Skin Regeneration by Stimulating Epidermal Growth and Dermal Neovascularization - Si Xiong (Nature Portfolio, 2017)
Abstract One of the key problems hindering skin repair is the deficiency of dermal vascularization and difficulty of epidermis regeneration, which makes it challenging to fabricate scaffolds that can biologically fulfill the requirements for skin regeneration. To overcome this problem, three-dimensional printing was used to fabricate a gelatin-sulfonated silk composite scaffold that was incorporated with basic fibroblast growth factor 2 (FGF-2) through binding with a sulfonic acid group (SO3) (3DG-SF-SO3-FGF). The efficacy and mechanism by which the 3DG-SF-SO3-FGF scaffolds promote skin regeneration were investigated both within in vitro cell culture and in vivo with a full-thickness skin defect model. The histological results showed that the gelatin-sulfonated silk composite scaffolds promoted granulation, and that incorporation of FGF-2 significantly enhanced the regeneration of skin-like tissues after implantation in rat skin defects for 14 and 28 days. Further investigations demonstrated that 3DG-SF-SO3-FGF scaffolds might stimulate dermal vascularization. These findings thus suggest that incorporation of FGF-2 into the 3D printed scaffolds is a viable strategy for enhancing skin regeneration.